Bayes classification of the text documents. Hierarchical clustering on the basis of frequent itemsets - Свириденко, Яна Сергіїна (Eastern-European Journal of Enterprise Technologies, 2010)
This article considers Bayes classification of text documents. For a more detailed analysis and practical use of the new approach for document clustering - hierarchical clustering based on frequent itemsets (FIHC), which is based on the idea of frequent itemsets.